Wariancja rzeczowników w "Nowym słowniku poprawnej polszczyzny PWN" - Ruszkowski, Marek (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
Linguistic variants are elements that are considered identically in terms of functionality, though they differ formally. The present article discusses variant forms of nouns. The study refers both to variants in the strict sense, i.e. identical in terms of function, and oscillating variants, i.e. those that differ in one quality, i.e. chronology, frequency, social range, stylistic character or the degree of expressiveness or emotiveness. The examples have been excerpted from "Nowy słownik poprawnej polszczyzny PWN" [The PWN New Dictionary of Correct Polish Usage]. The collected material has been classified into several groups depending on the relations between variants defined by means of qualifiers and abbreviations. Formal and linguistic expressions of noun variantivity are also presented. The examples under scrutiny indicate that the linguistic norm (standard) accepts far more nominal variant forms than the linguistic custom presents as it has sanctioned only a certain part of the analysed examples. A detailed and thorough study on the functioning of nominal variants in the linguistic custom is, however, difficult to carry out.
Variantivity of nouns in "Nowy słownik poprawnej polszczyzny PWN"
Keywords: Wariancja (wariantywność) językowa; Rzeczownik; Leksykografia